Pemanfaatan Media Papan Kotak Dalam Meningkatkan Hasil Belajar Matematika Pada Materi Satuan Panjang Kelas III UPTD SDN 104 Inpres Makkaraeng - Wijayanti, Arini; Nurdesiana; Firdaus , Andi Mulawakkan (Jurnal Guru Pencerah Semesta, 2024)
Based on the initial data in the class III SDN 104 Inpres Makkaraeng, found problems in mathematical learning on the unit material is less student understanding due to the absence of learning media, so students are inactive, bored not even master the material. The purpose of this study is to know 1) the process of using the Board of Media Board on Mathematical Lesson Matches Limit and 2) Increasing Student Learning Results on Large Unit Machine through the use of media board. The research used used is the course of classroom action (PTK) there are 2 cycles. In each cycle consists of planning, coercion, observation and reflection. The location of the study was SDN 104 Inpres Makkaraeng, Mandai District, Maros Regency who was mended in September to November 2023.. This research instrument is an interview sheet, observation sheet, and initial exam (cycle I) and final exam (cycle II). The results showed the use of boxed media boards can improve student learning outcomes that achieved values above KKM (75) with the percentage of solvent learning results, student solvement by 69% with uncontentable category. There was an increase in cycle II with a student solvent score of 95.6%. In cycle I, many students who are completely numbered 16 and not completed amounted to 7 students. The average student learning outcome in the II cycle of 85.86 and is included in the CTM Security category. In addition, in the table can be known that the percentage of KKM completeness is 95.6% with the number of 22 students who are completed and only 1 unpondent student. Based on the research it can be concluded that learning unlimited mathematical learning with the utilization of the long-term board box can be successful, so it can be made one alternative solution to lift the learning of mathematics in SDN 104 Inpres Makkaraeng.